Liquiditas, Profitabilitas dan Debt to Aseets Rasio pada Perusahaan Advertising, Media dan Printing yang Terdaftar di Bursa Efek Indonesia - Tumanggor, Arief Hidayat (Jurnal EMT KITA, 2023)
Capital structure decisions are an important aspect of complex financial management because they consider the relationship between long-term debt and equity, with the primary goal of maximizing owner wealth. property. This study aims to analyze the effects of current ratio and return on assets on capital structure (DAR) in advertising, media and printing companies listed on the Stock Exchange. Indonesia (BEI). Using the combined method, data were analyzed using the classical hypothesis method, multiple linear regression, t-test (partial), f-test (simultaneous) and coefficients determined using SPSS software. version 16. The results show that, in Part, the current ratio has no significant influence on capital structure (DAR) (sig 0.076), while the return on assets has a significant influence including capital structure (DAR) (sig 0.025). At the same time, both factors quick ratio and return on assets have a significant influence on capital structure (DAR) (sig 0.011). The coefficient of determination (R-Square) of 0.956 shows that about 95.6% of the variation in capital structure (DAR) can be explained by changes in the current ratio and return on assets, while the remaining 4.4% were influenced by other factors not investigated in Ceci's study. This study provides important information for financial managers to manage a company's capital structure more effectively.